Structure of yeast 5-aminolevulinic acid dehydratase complexed with the inhibitor 5-hydroxylevulinic acid - Erskine, P. T.; Coates, L.; Newbold, R.; Brindley, A. A.; Stauffer, Frederic; Beaven, G. D. E.; Gill, R.; Coker, A.; Wood, S. P.; Warren, M. J.; Shoolingin-Jordan, P. M.; Neier, Reinhard; et al. (My University, 2005)
The x-ray crystal structure of 5-aminolevulinate dehydratase (ALAD) of yeast complexed with the competitive inhibitor, 5-hydroxylevulinic acid, was detd. at a resoln. of 1.9 Å. The structure showed that the inhibitor was bound by a Schiff-base link to one of the invariant active site Lys residues (Lys-263). The inhibitor appeared to bind in 2 well-defined conformations and the interactions made by it suggested that it is a very close analog of the substrate, 5-aminolevulinic acid (ALA). [on SciFinder(R)]
Keywords: Yeast (crystal structure of yeast 5-aminolevulinate dehydratase complexed with 5-hydroxylevulinic acid); Enzyme functional sites (inhibitor-binding; of 5-aminolevulinate dehydratase of yeast); Crystal growth; Crystal structure (of 5-aminolevulinate dehydratase of yeast complexed with 5-hydroxylevulinic acid); Conformation (protein; of 5-aminolevulinate dehydratase of yeast complexed with 5-hydroxylevulinic acid); aminolevulinate dehydratase yeast hydroxylevulinate complex crystal structure